ENGLISH FOR ECONOMICS AND FINANCE (Conferencea, 2021)
This tutorial is intended for students of the economic profile of technical universities. The structure of the manual is determined by the professional aspects of a specialist in the field of economics and finance. All information of the article has a single structure and include the following blocks: Before you start (introduction), Reading (texts in the specialty), Language (formal training exercises), Speaking (communicative-meaningful exercises), Writing (tasks aimed at developing skills written speech), Vocabulary (basic vocabulary of each section).